Lucifer. The complete second season [videorecording (DVD)] - Ellis, Tom, 1978-; German, Lauren, 1978-; Woodside, D. B. (David Bryan), 1969- (Warner Bros. Home Entertainment, 2017)
In Season Two, LAPD Detective Chloe Decker and Lucifer Morningstar are back solving murders on L.A.'s white-hot streets, with their relationship growing deeper, closer, and more awkward for them both. To add fuel to the fire, Lucifer's mum, Charlotte, escapes Hell, bringing along a ton of emotional baggage: She wants back what was stolen from her. Now Lucifer and his angel brother, Amenadiel, with whom Lucifer has serious sibling issues, must work together to find mommy dearest.